Nova perspectiva constitucional dos meios privados de resolução de conflitos - Diógenes, George Lucas Souza (Universidade Federal Rural do Semi-Árido, 2017)
The (dis)satisfaction of the people who are subjected to a certain legal order with the Justice is not a simply barren factor that fills statistics, which are usually avaliable to possibly interested people. It is a feeling that echoes rather in the legitimation and stability of any social order. The relevance of the commitment in understanding and solving the main failures which are responsible for affecting the fruition of a fair juridical order lies precisely at this point. A common method avaliable is the employment of private ways to resolve conflicts – whose pertinence is competely appropriate to analyse. Therefore, we work under the hypotheticaldeductive method and the literature and documents review, based on the fundamentals of the sovereignty and the justice to finally culminate in the possibility of including those private methods in the protective bations (eternity clauses) of the 1988 Brazilian Constitution. Thus, offering autonomy permanently to the individual and a steadfast project to the society, leading to the framing of a new mindset.
Artigo Acadêmico
Keywords: Cláusula pétrea; Conflitos; Justiça; Vias privadas; Ordenamento jurídico; Conflitcts; Eternity clause; Juridical order; Justice; Private ways; CIENCIAS SOCIAIS APLICADAS::DIREITO